2012
DOI: 10.11144/javeriana.upsy12-1.eeas
|View full text |Cite
|
Sign up to set email alerts
|

Elaboración de una Escala de Apoyo Social (EAS) para adultos

Abstract: El apoyo social se ha definido como las transacciones interpersonales instrumentales que implican ayuda en todas sus vertientes, tales como emocional, económica, implícita, explícita, etc. La presente investigación tuvo como objetivo elaborar una escala que midiera el apoyo social para la población mexicana en situación de pobreza. Se tomaron como base dos instrumentos: la Multidimensional Scale of Perceived Social Support y el Inventory of Socially Supportive Behaviors. La muestra la conformaron 913 personas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
2
0
4
Order By: Relevance
“…Studies have shown that HIV-related stigma usually causes decreased social support following HIV diagnosis and worsens mental health (Garrido-Hernansaiz & Alonso-Tapia, 2017). Social support is important for OBWLH to effectively navigate physical, financial, and emotional challenges that occur with HIV progression and management (Palomar, Matus, & Victorio, 2013). Social support is an essential factor for good quality of life among people living with HIV (Remor et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that HIV-related stigma usually causes decreased social support following HIV diagnosis and worsens mental health (Garrido-Hernansaiz & Alonso-Tapia, 2017). Social support is important for OBWLH to effectively navigate physical, financial, and emotional challenges that occur with HIV progression and management (Palomar, Matus, & Victorio, 2013). Social support is an essential factor for good quality of life among people living with HIV (Remor et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Apoyo Social: La Escala de Apoyo Social para Adultos (EAS) es un auto reporte de 21 ítems (e.g. Cuento con al menos una persona que se preocupa por mi bienestar) desarrollado y validado en población mexicana por Palomar-Lever et al (2013). Los ítems se responden utilizando un Escala tipo Likert de cuatro puntos que van de 1 = "Totalmente en desacuerdo" a 4 = "Totalmente de acuerdo".…”
Section: Instrumentosunclassified
“…The objective of this study was to validate the scores of the Resilience Scale for Mexican adults based on the survey carried out by Palomar and Gómez (2010) and to adapt it to the context of young adolescents from higher secondary education of Conalep 1 and 2 in Ciudad Juárez, Chihuahua, Mexico. For this, the Factors' Exploratory Analysis of and the Cronbach's Alpha Analysis were carried out where the inference of the scores and the psychometric properties could be made to be able to measure the resilience constructs in question: 1) Strength and self-confidence themselves, 2) Social competence, 3) Family support, 4) Social support, and 5) Structure.…”
Section: Introductionmentioning
confidence: 99%